Insights into the sex life of an endemic riverine fish from F iji: P rotandrous hermaphroditism in the orange‐spotted therapon— Mesopristes kneri ( B leeker, 1876) - Lekima K. F. Copeland; Renee Hill‐Lewenilovo; Kimberly E. K. Samson; Monal M. Lal; Brian L. Stockwell (Journal of Fish Biology, 2026)
The orange‐spotted therapon, Mesopristes kneri , is an ecologically and economically important riverine fish endemic to Fiji, yet its life history and reproductive biology remain poorly understood. This study examined the reproductive biology, life history and sexual development of M. kneri to support conservation and fisheries management. From April 2022 to May 2023, field‐based histological analyses were conducted on 118 individuals sampled from the Navua River, comprising 86 females, 24 males, five transitional individuals and three sexually undifferentiated individuals. The findings support protandrous hermaphroditism, potentially through a monogynic pathway, as indicated by the absence of functional females in smaller size classes, size‐specific sex ratios and histological evidence of transitional gonads. Sexual dimorphism was evident, with females attaining larger body sizes than males. The length predicted to comprise 50% mature individuals was estimated at 20.39 cm SL, while the fitted transition model estimated X50, the length predicted to comprise 50% males, at 20.14 cm SL. Histological analyses confirmed asynchronous oocyte development and the presence of transitional gonads containing regressing testicular tissue and developing ovarian structures. The transitional gonads of M. kneri exhibited a delimited configuration, with a connective tissue barrier separating testicular and ovarian regions. The sampled population also showed a strongly female‐biased sex ratio, particularly in larger size classes, and a positive relationship between batch fecundity and female size. These findings indicate that management strategies should consider the protection of larger, highly fecund females while also maintaining sufficient smaller and intermediate‐sized functional males to support reproductive success. This study provides critical baseline information on the reproductive biology of M. kneri and contributes to the development of conservation and fisheries management strategies for Fiji's riverine ecosystems.

The carbon cost of the 2019–20 Australian fires varies with fire severity and forest type - Rachael H. Nolan; Luke Collins; Rebecca K. Gibson; Stephanie A. Samson; Katherine T. Rolls; Kirsty Milner; Belinda E. Medlyn; Owen F. Price; Anne Griebel; Brendan Choat; Mingkai Jiang; Matthias M. Boer (Global Ecology and Biogeography, 2022)
Aim To estimate loss of above‐ground carbon (AGC) and conversion of live carbon to dead carbon following understorey and canopy fire. Location South‐eastern Australia. Time period 2019–2020. Major taxa studied Four widespread resprouting eucalypt forests. Methods Above‐ground carbon was measured in 15 plots in each of four forest types one‐year post‐fire. We also assessed topkill, that is, trees subject to canopy loss that failed to resprout epicormically. Results While canopy fire was associated with greater declines in AGC than understorey fire, this was only statistically significant for only one forest type, where AGC declined from 154 to 85 Mg C ha −1 following canopy fire. Significant post‐fire increases in dead AGC were observed in one forest type, where dead carbon increased from 22 to 60% after canopy fire. Topkill of trees following canopy fire (48–78% of stems) was higher than topkill after understorey fire (36–53% of stems) and in unburnt forest (12–55%). Topkill occurred primarily in small‐diameter stems. Consequently, there was no effect of fire on the proportion of dead AGC in trees, with the exception of the forest with lowest productivity (i.e., lowest biomass) and lowest annual rainfall, where dead tree carbon increased from 8% in unburnt forest to 13 and 53% after understorey and canopy fire, respectively. AGC in understorey vegetation and coarse woody debris was similar or lower in burnt compared with unburnt forest. Litter carbon was significantly lower and pyrogenic carbon significantly higher in burnt forest, with no difference between understorey and canopy fire. Main conclusions While increased fire severity was associated with increased changes to carbon stocks, there were differences among forest types. Specifically, the driest forest type had the highest rates of topkill following canopy fire. These results highlight the importance of spatial variability in fire severity and forest type in determining the effects of fire on carbon stocks.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Diffusion pathways of Fe2+ and Fe3+ during the formation of ferrian chromite: a µXANES study - F. Gervilla; M. P. Asta; l. Fanlo; D. Grolimund; D. Ferreira-Sánchez; V. A. Samson; D. Hunziker; V. Colas; J. M. González-Jiménez; T. N. Kerestedjian; I. Sergeeva (Contributions to Mineralogy and Petrology, 2019)

Improving propagation methods of Gnetum africanum and G. buchholzianum from cuttings for rapid multiplication, domestication and conservation - Oumar Doungous; Emile Minyaka; Samson D. Medza-Mve; Apollin F. Medueghue; Mercy A. Ngone; Claude Simo; Armand M. Nsimi (Agroforestry Systems, 2019)

Prioritisation of native legume species for further evaluation as potential forage crops in water-limited agricultural systems in South Africa - Francuois L. Müller; Lincoln M. Raitt; Samson B. M. Chimphango; M. Igshaan Samuels; Clement F. Cupido; J. Stephen Boatwright; Richard Knight; Marike Trytsman (Environmental Monitoring and Assessment, 2017)

Inbreeding and inbreeding depression of early life traits in a cooperative mammal - JOHANNA F. NIELSEN; SINEAD ENGLISH; WILL P. GOODALL‐COPESTAKE; JINLIANG WANG; CRAIG A. WALLING; ANDREW W. BATEMAN; TOM P. FLOWER; ROBERT L. SUTCLIFFE; JAMIE SAMSON; NATHAN K. THAVARAJAH; LOESKE E. B. KRUUK; TIM H. CLUTTON‐BROCK; et al. (Molecular Ecology, 2012)
Mating between relatives often results in negative fitness consequences or inbreeding depression. However, the expression of inbreeding in populations of wild cooperative mammals and the effects of environmental, maternal and social factors on inbreeding depression in these systems are currently not well understood. This study uses pedigree‐based inbreeding coefficients from a long‐term study of meerkats ( Suricata suricatta ) in South Africa to reveal that 44% of the population have detectably non‐zero ( F > 0) inbreeding coefficients. 15% of these inbred individuals were the result of moderate inbreeding ( F ≥ 0.125), although such inbreeding events almost solely occurred when mating individuals had no prior experience of each other. Inbreeding depression was evident for a range of traits: pup mass at emergence from the natal burrow, hind‐foot length, growth until independence and juvenile survival. However, we found no evidence of significant inbreeding depression for skull and forearm length or for pup survival. This research provides a rare investigation into inbreeding in a cooperative mammal, revealing high levels of inbreeding, considerable negative consequences and complex interactions with the social environment.

Impact of durum wheat milling on deoxynivalenol distribution in the outcoming fractions - G. Ríos; N. Zakhia-Rozis; M. Chaurand; F. Richard-Forget; M.F. Samson; J. Abecassis; V. Lullien-Pellerin (Food Additives & Contaminants: Part A, 2009)

Potential Use of the Plant Antioxidant Network For Environmental Exposure Assessment of Heavy Metals in Soils - E. Meers; A. Ruttens; W. Geebelen; J. Vangronsveld; R. Samson; K. Vanbroekhoven; M. Vandegehuchte; L. Diels; F. M. G. Tack (Environmental Monitoring and Assessment, 2006)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)